Fighting Against Climate Change: Denmark’s Effort in Reducing Global Carbon Emissions - Lintang Sumunaring Tyas; Havidz Ageng Prakoso (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2022)
The problem of climate change is a global threat, which is driven by the production of global carbon emissions that continue to increase every year, reaching 36.4 billion metric tons in 2020. If this continues, climate change will cause various negative impacts on the lives of the global community in the field of environmental, economic, social, and health. Therefore, countries must commit and make real efforts to reduce global carbon emissions each year. Denmark is one of the countries that has big ambitions to reduce global carbon emissions, so it makes various efforts at the national, regional, and international levels, and becomes a role model for other countries. The purpose of this research is to find out Denmark's efforts to reduce global carbon emissions. The research used a qualitative descriptive method by using Green Diplomacy Concept in describing Denmark’seffort. The results obtained are that Denmark has succeeded in becoming a country that has significantly reduced national carbon emission production, which was then continued by carrying out The Green Frontline Mission program in various countries, encouraging carbon emission reduction policies in the European Union, becoming chairman of COP26, and establishing the Beyond organization. Oil & Gas Alliance (BOGA). Denmark's various efforts in suppressing the production of global carbon emissions are part of green diplomacy which not only achieves the national interest but also the public interest, namely solving the problem of climate change.